Ruritania by the Sea : Detection by the Seaside in Dorothy L. Sayers’s Have His Carcase - Hudácskó, Brigitta (Hungarian Journal of English and American Studies, 2021)
Seaside resorts frequently served as locations of murder mysteries in Golden Age detection fiction, since these destinations could provide a diverse clientele, confined to manageably small groups essential to classic detective stories. The fictional seaside town of Wilvercombe serves as the location of Dorothy L. Sayers’s detective novel Have His Carcase (1932), in which Lord Peter Wimsey and detective-story writer Harriet Vane investigate the case of a man found dead on the beach. The location of the body turns out to be a source of confusion: while the detectives expect a traditional locked-room mystery to unfold (albeit in an open-air setting), the death cannot be resolved until the detectives realize that they are working in the wrong genre: instead of a clue-puzzle mystery, they are trapped in a Ruritanian romance, with outlandish tales of intrigue, unlikely members of the Russian aristocracy, and exaggerated and oppressive performances of heterosexual romance. (BH)